The 2004 Viet Nam migration survey : (Nhà xuất bản Hà Nội, 2006)
Executive summary: Registration and migrant status; the diffilulties faces by migrants; the effects of migrant status on housing conditions; the effects of migrant stastus on labour market outcomes; migrant networks, labour market outcomes and housing; policy implication.